Pengendalian Kualitas Pelayanan melalui Analisis GAP dengan Instrumen Servqual (Studi di Unika Widya Mandala Surabaya) - Widyarini, Lydia Ari; Supriharyanti, Elisabeth (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2003)
The strong competitiveness in higher education make the Widya Mandala Surabaya Catholic University (WMSCU) has to evaluate the operational process. So it could take the information which used to control the operational process through the strategic for adapted itself with the fluctuatif changes. This research is descriptive-evaluative used the gap analysis (Parasuraman-et al, 19S6. 1he-re're Jive variables: tangtbte, reliability, responsiveness, assurance and empathy. Then umbero f to^pl